Radiopacity evaluation of a new root-end filling material (NREFM) with two types of radiopacifiers in comparison to pro-root MTA and Portland cement - Ali Akhavan; Elahe Shafiei Rad; Mozhdeh Mehdizadeh; Seyed Behrouz Mousavi; Jalil Modaresi (Isfahan University of Medical Sciences, 2012)
Introduction: Recently a new root-end filling material (NREFM), referred to as Cold Ceramic (CC), has been introduced; different studies have shown its biocompatibility, low cytotoxicity and good sealability. One of the disadvantages of CC is its low radiopacity in clinical procedures. The aim of this study was to evaluate radiopacity of CC by incorporating different radiopacifiers (Bi2O3, BaSo4) in comparison to Pro-root MTA and PC. Materials and Methods: In this in vitro study 7 groups of materials (Group 1: 0.9 NREFM + 0.1 gr Bi2O3; Group 2: 0.8 gr NREFM + 0.2 gr Bi2O3; Group 3: 0.9 NREFM + 0.1 gr BaSo4; Group 4: 0.8 gr NREFM + 0.2 gr BaSo4; Group 5: NREFM; Group 6: Pro-root MTA; Group 7: PC) were mixed with 0.3 mL of distilled water and placed in Teflon rings measuring 10 mm in internal diameter and 1 mm in thickness, based on ISO 6876/2001 and allowed to set. The samples were placed on PSP cassettes adjacent to a step-wedge graduated aluminum plate and radiographed. The radiographic density was determined using Digora and Scannora software programs. Data were analyzed by SPSS using Kruskal-Wallis and Mann-Whitney tests (α = 0.05). Results: Group 6 exhibited the highest radiopacity (6.85 mm Al) and PC samples exhibited the lowest radiopacity (2.74 mm Al). Conclusion: All the materials tested exhibited acceptable radiopacity except for PC. A combination of 0.9 gr NREFM + 0.1 gr Bi2O3 has radiopacity comparable to that of Pro-root MTA. Key words: Aluminum, Mineral trioxide aggregate, Portland cement, Retrograde root-end obturation.